Antidromic Analog Signaling - Trigo, Federico F. (Frontiers in Cellular Neuroscience, 2019)
Analog signaling describes the use of graded voltage changes as signals in the axonal compartment. Analog signaling has been described originally in invertebrates but more recent work has established its presence in the mammalian brain. In recent years, many different groups have contributed to the understanding of the physiological significance of analog signaling from a cellular perspective (for a recent review the reader may take a look at the work by Zbili and Debanne in this Frontiers in Neuroscience Special Issue). The great majority of the experimental work related to analog signaling however, concerns the propagation of subthreshold voltage changes from the soma to the axon. Much less attention has been paid to the propagation of subthreshold voltage changes in the opposite direction, from the axon to the soma, or to the propagation of local signals within the axon. In this mini review we will describe these other variants of analog signaling that we call here “antidromic” coupling and “local” coupling.